2019
DOI: 10.1111/obes.12310
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Empirical Relevance of the ‘Saving for a Rainy Day’ Hypothesis in US Metro Areas

Abstract: The joint implication of the consumption Euler equation and cointegration between income and consumption is that savings predict future income declines, the ‘saving for a rainy day’ hypothesis. The empirical relevance of this hypothesis plays a key role in discussions of fiscal policy multipliers, and it holds under the null that the permanent income hypothesis is true. We find little support for this hypothesis using time series data for the 100 largest US Metropolitan Statistical Areas for the period 1980q1–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 88 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…If this is not the case, the vector autoregression is misspecified and the impulse responses that it yields are potentially biased. 16 Coibion (2012) has drawn attention to the fact that in Romer and Romer's (2004) results, the peak responses of industrial production and unemployment to a change in the federal funds rate are roughly six times larger than in a standard monetary vector autoregression. In the online appendix to this paper, we revisit this issue by estimating the response of industrial production and the real interest rate to monetary shocks in six different ways.…”
Section: What Do We Do With These Shocks?mentioning
confidence: 99%
“…If this is not the case, the vector autoregression is misspecified and the impulse responses that it yields are potentially biased. 16 Coibion (2012) has drawn attention to the fact that in Romer and Romer's (2004) results, the peak responses of industrial production and unemployment to a change in the federal funds rate are roughly six times larger than in a standard monetary vector autoregression. In the online appendix to this paper, we revisit this issue by estimating the response of industrial production and the real interest rate to monetary shocks in six different ways.…”
Section: What Do We Do With These Shocks?mentioning
confidence: 99%
“…In recent years, in particular following the global financial crisis that became an income and job crisis, several empirical contributions have recognised the importance of debt and of housing prices in the complex processes that drive economic fluctuations in advanced economies with liberalised credit markets. For example, three studies with consistent findings for the US saving rate dynamics were presented by Carroll et al (2012), Mian et al (2013) and Anundsen and Nymoen (2019). Using a dataset with long historical time series for 14 advanced economies, Jordà et al (2013) concluded that financial factors play an important role in the modern business cycle (see also Anundsen et al (2016)).…”
Section: Introductionmentioning
confidence: 85%
“…We follow Eitrheim et al . (2002) and Anundsen and Nymoen (2019) and formulate the ‘saving for a rainy day’ hypothesis asytctfalse∑i=1ρiEtΔyt+i+ς,where the saving ratio, StYLt, is approximated by the logarithms of income to consumption ratio, y t − c t , and labour income, yl t + i , is replaced by income, y t + i . An important time series property, which we shall utilize in the nested CVAR, is that the saving ratio is stationary, I (0), and thus that income and consumption are cointegrated with a coefficient equal to one when income is non‐stationary, I (1).…”
Section: Theoretical Backgroundmentioning
confidence: 99%